2019
DOI: 10.5194/isprs-annals-iv-5-w2-89-2019
|View full text |Cite
|
Sign up to set email alerts
|

Land Surface Temperature Profiling and Its Relationships With Land Indices: A Case Study on Lucknow City

Abstract: Abstract. Globally, 54.5% of the total population was living in urban settings in 2016 and a projection indicates that if the same trend goes, then this population will be 60% in 2030. Natural land has been converted to impervious space rapidly which is altering the climate change. The main focus of the present paper is the study of Land Surface Temperature (LST) dynamics and its relationship with Land Indices, viz., Normal Difference Vegetation Index (NDVI) which is found negative, Normal Difference Built-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Land surface emissivity (LSE) is an important parameter to calculate LST [62,63]. NDVI threshold (NDVI THR ) method was used to calculate LSE because it can differentiate pixels of vegetation, water, and soil significantly [64].…”
Section: Land Surface Emissivitymentioning
confidence: 99%
“…Land surface emissivity (LSE) is an important parameter to calculate LST [62,63]. NDVI threshold (NDVI THR ) method was used to calculate LSE because it can differentiate pixels of vegetation, water, and soil significantly [64].…”
Section: Land Surface Emissivitymentioning
confidence: 99%
“…A healthy environment condition is characterized by the positive values of NDVI. NDVI plays an important role in urban climate analysis (Guha et al, 2020;M. O. Sarif & Gupta, 2019).…”
Section: 3 Lst Estimationmentioning
confidence: 99%
“…Based on the overall assessment of Table 6, the outputs expose that the maximum increase of LST is related to bare land, built-up, and urban areas, whereas the minimum increase of LST is related to the water body and vegetation areas. This is related to the high evapotranspiration phenomenon from vegetation areas which precisely play important role in the reduction of land surface temperature (Kamali Maskooni et al, 2021;M. O. Sarif & Gupta, 2019).…”
Section: Relationship Between Land Use/land Cover and Lstmentioning
confidence: 99%
“…Some studies rigorously found similar facts in Taipei city of Taiwan [15], Phoenix city of the United States of America (USA) [16], Singapore [10], Dhaka city of Bangladesh [17], Kathmandu valley of Nepal [18], Nanjing city of China [19], Beijing city of China [20], Tokyo city of Japan [21], Tehran city of Iran [13], 70 selected cities of Europe [22], Hong Kong [23], Baltimore-DC metropolitan area of the USA [24], and Cairo city of Egypt [25]. At the same time, researchers have discussed how their changing aspects affect and transform the environment of the city landscape in various Indian cities, such as Kolkata [26], Delhi and Mumbai [27], Chandigarh [28], Hyderabad [29], Noida [30], Lucknow [31], and Raipur [32]. Mal et al (2020) conducted a study on the relationship of LST with LULC and elevation in the Ganga River basin, which includes major cities such as Kolkata, Patna, Allahabad (now Prayagraj), Varanasi, Lucknow, Kanpur, New Delhi, and Kathmandu during 2001-2019 using 1 km of MODIS Terra datasets [33].…”
Section: Introductionmentioning
confidence: 99%